2020
DOI: 10.1513/annalsats.201910-767oc
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Strain, Brain Natriuretic Peptide, and Mortality in Congenital Diaphragmatic Hernia

Abstract: Rationale: Brain-type natriuretic peptide (BNP) correlates with pulmonary hypertension as demonstrated by echocardiogram in congenital diaphragmatic hernia (CDH); however, its association with right ventricular (RV) function and mortality is unknown.Objectives: To characterize the relationships between echocardiogram-derived RV strain, BNP, and mortality in diaphragmatic hernia. Methods:We performed a single-center retrospective cohort study of infants with CDH and at least one BNP-echocardiogram pair within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In cohort studies early RV dysfunction is associated with prolonged duration of respiratory support, increased mortality and ECMO use (49,(59)(60)(61). In a recent large multi-center registry analysis of cardiac function in the first 48 h of life RV dysfunction was present in 34% of CDH cases either in isolation in combination with LV dysfunction, and was associated with increased mortality and ECMO use (62).…”
Section: Right Ventricle Dysfunction In Congenital Diaphragmatic Herniamentioning
confidence: 99%
See 3 more Smart Citations
“…In cohort studies early RV dysfunction is associated with prolonged duration of respiratory support, increased mortality and ECMO use (49,(59)(60)(61). In a recent large multi-center registry analysis of cardiac function in the first 48 h of life RV dysfunction was present in 34% of CDH cases either in isolation in combination with LV dysfunction, and was associated with increased mortality and ECMO use (62).…”
Section: Right Ventricle Dysfunction In Congenital Diaphragmatic Herniamentioning
confidence: 99%
“…BNP has a short halflife complicating measurement, but in CDH has been shown to be associated with pulmonary hypertension, need for ECMO, predictive of adverse outcome at 1 month of age, Table 4 (84,85). Recently Avitabile et al also demonstrated that BNP was associated with impaired RV strain after CDH repair, though not in the pre-operative period (61).…”
Section: Biomarkers Of Cardiac Function In Congenital Diaphragmatic H...mentioning
confidence: 99%
See 2 more Smart Citations
“…Echocardiographic studies of early RV function have demonstrated RV systolic and diastolic dysfunction, and evidence of interdependent impairment of LV function (47,48). Furthermore, early RV dysfunction pre-and post CDH repair have been shown to be associated with adverse outcomes, including increased mortality, ECLS use and length of hospitalization in survivors, in single center cohorts as well as large registry-based analyses (49)(50)(51).…”
Section: The Rv In Ph Disease: Animal Modelsmentioning
confidence: 99%